Graduate attribute for minimising environmental harm – Assessing effectiveness in the graduates' workplaces. (20th February 2019) - Holdsworth, Sarah; Thomas, Ian; Wong, Peter; Sandri, Orana; Boulet, Mark; Chester, Andrea; McLaughlin, Patricia
Abstract: Over recent times concern about the physical environment has fluctuated. Even after the coverage of environment and sustainability issues in the education of many professions, a decline of community concern suggests that the potential for the inclusion of environmental issues in the work of professionals could be limited. This situation raises the question of whether recent graduates have the ability, through their workplaces, to act to minimise environmental harm. To assess this ability, based on the Theory of Planned Behaviour, a survey instrument was developed and tested on a sample of graduates, of an Australian university, associated with the building and construction fields. Results indicated, firstly, that the model provided a valid approach to the assessment of influences on a graduate's behaviour. Secondly, that factors associated with their workplaces are very influential, especially support from their employers and clients. Further, behavioural enablers are especially important influences on behaviour: specifically the resources available to the graduate, workplace support and assistance, and the scope and power associated with the graduate's role. These findings provide insights for the curriculum and pedagogy that is needed if graduates are to enter the workforce and be effective in minimising environmental harm from their professional activities.